Analisis pembelajaran menulis puisi peserta didik kelas IV sekolah dasar - Utami, Fadzilah Nisa Siwi; Winarni, Retno; Sriyanto, Muhammad Ismail (Universitas Sebelas Maret, 2023)
This study aims to describe and explain planning, implementation and assessment held by the teacher in writing poetry learning for grade IV student in SD Negeri 6 Bendungan for the 2022/2023 academic year. This research is a qualitative research with a descriptive approach. Data collection techniques used are interviews, observation, and documentation. The validity of the data is tested using triangulation method using source triangulation and metodological triangulation. The data is analyze using interactive analysis method, which consists of 3 stages, which are: data reduction, data presentation, and drawing conclusions/verification. The results showed that (1) planning of writing poetry learning in grade IV SD Negeri 6 Bendungan begins with the preparation of learning objectives (ATP), making teaching modules (MA), and determining the criteria for completing learning objectives (KKTP). (2) The implementation of write poetry learning is carried out for 3 meetings. The first meeting was in the form of initial assessment activities, the second was group assignments, and the third was individual assignments by producing a product in the form of poetry. (3) Assessment of learning is carried out by the teacher using assessment, diagnostic, formative and summative